2001
DOI: 10.1152/ajpgi.2001.281.3.g752
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gastric emptying by acarbose is correlated with GLP-1 response and accompanied by CCK release

Abstract: We investigated the effect of acarbose, an alpha-glucosidase and pancreatic alpha-amylase inhibitor, on gastric emptying of solid meals of varying nutrient composition and plasma responses of gut hormones. Gastric emptying was determined with scintigraphy in healthy subjects, and all studies were performed with and without 100 mg of acarbose, in random order, at least 1 wk apart. Acarbose did not alter the emptying of a carbohydrate-free meal, but it delayed emptying of a mixed meal and a carbohydrate-free mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 46 publications
5
40
2
Order By: Relevance
“…In this study, we demonstrated that combination therapy decreased the increment in the total PYY level induced by the administration of miglitol. PYY 1-36 is considered to be increased by the administration of miglitol, based on its pharmacological effect, and also to be increased by the administration of vildagliptin, as previously reported [28]. Therefore, the combination therapy increased the PYY 1-36 level and decreased the PYY 3-36 level, leaving the total PYY level unaffected when compared with that of the control group.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In this study, we demonstrated that combination therapy decreased the increment in the total PYY level induced by the administration of miglitol. PYY 1-36 is considered to be increased by the administration of miglitol, based on its pharmacological effect, and also to be increased by the administration of vildagliptin, as previously reported [28]. Therefore, the combination therapy increased the PYY 1-36 level and decreased the PYY 3-36 level, leaving the total PYY level unaffected when compared with that of the control group.…”
Section: Discussionsupporting
confidence: 54%
“…The administration of acarbose reportedly increased the postprandial CCK level in healthy men, although the mechanism responsible for this increase was unclear [28]. Unlike acarbose, miglitol is partially absorbed from the proximal portion of the small intestine [29], and this leads to a decrease in absorbed carbohydrates from the proximal portions of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acarbose (28,29), voglibose (30), and miglitol (31) have been shown to enhance the GLP-1 response in healthy volunteers and type 2 diabetic patients. It is possible that the difference of GLP-1 levels between our study and these papers is due to the difference of the determination methods of GLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of glucose in rat, pig, and dog (13)(14)(15) or carbohydrate in human (41) directly into the ileal lumen triggers GLP-1 secretion. Retarding sugar absorption in humans using the ␣-glucosidase inhibitor acarbose results in earlier and larger increments in plasma GLP-1 levels, which has been attributed to the greater supply of sugar reaching distal populations of L-cells (42,43). The reactive hypoglycemia observed in dumping syndrome, which is associated with the arrival of high concentrations of sugar in the distal small intestine and colon, has also been attributed to increased GLP-1 release (44,45).…”
Section: Discussionmentioning
confidence: 99%